2012
DOI: 10.1097/ico.0b013e31823f8d9e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Punctal Occlusion on Tear Menisci in Symptomatic Contact Lens Wearers

Abstract: Punctal occlusion transiently increased tear menisci in symptomatic and asymptomatic lens wearers, with a longer duration in the symptomatic group. For both symptomatic and asymptomatic lens wearers, the increased meniscus volume was associated with improved ocular comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…TMH measurement has been used to assess the effect of punctal plug insertion. Several publications 6,14,15 demonstrated that TMH increased immediately after plug insertion, with results very similar to our study. The immediate increase in TMH after punctal occlusion showed tear secretion still remaining in many patients, even those with severe ADDE, but tear drainage had a deleterious effect in these cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TMH measurement has been used to assess the effect of punctal plug insertion. Several publications 6,14,15 demonstrated that TMH increased immediately after plug insertion, with results very similar to our study. The immediate increase in TMH after punctal occlusion showed tear secretion still remaining in many patients, even those with severe ADDE, but tear drainage had a deleterious effect in these cases.…”
Section: Discussionsupporting
confidence: 92%
“…For severe dry eye, inferior and superior punctal occlusion has better efficacy than simple inferior occlusion. 6 A meta-analysis of 18 studies 7 concluded that silicone plugs could reduce symptoms quickly after insertion in patients with severe dry eye disease but with low evidence. However, some authors have reported spontaneous loss of plugs in one third of patients within 1 month after insertion, along with complications such as excessive tearing, increased inflammation of the ocular surface, plug migration, canaliculitis, and pyogenic granuloma.…”
mentioning
confidence: 99%
“…Li et al used ultrahigh resolution optical coherence tomography to see the effect of punctal occlusion on tear menisci in contact lens wearers with and without symptoms of dry eyes. Tear menisci increased transiently in both symptomatic and asymptomatic lens wearers and increased for a longer duration in symptomatic wearers [ 50 ]. A randomized controlled clinical trial evaluated the effect of punctal occlusion in dry eye contact lens wearers using a self-assessment questionnaire and evaluation of pre- and postlens tear film thickness.…”
Section: Methodsmentioning
confidence: 99%
“…UHR-OCT can perform a dynamic evaluation of contact lens movement with blinking and shifting gaze [42]. Soft contact lenses usually overlap 2 mm on the bulbar conjunctiva, but can displace further and overlap 4 to 5 mm onto the bulbar conjunctiva during blinking [43].…”
Section: Contact Lens Fittingmentioning
confidence: 99%